Banded Net-Winged Beetle, Calopteron discrepans (Newman) (Insecta: Coleoptera: Lycidae) - Donald W. Hall; Marc A. Branham (EDIS)
EENY-413, a 4-page illustrated fact sheet by Donald W. Hall and Marc A. Branham, is part of the Featured Creatures collection. It describes this colorful black and orange net-winged woodland beetle common through much of the eastern U.S., its distribution, description, and life cycle and biology. Includes selected references. Published by the UF Department of Entomology and Nematology, July 2007.